Quality of life and its associated factors among patients with type 2 diabetes mellitus in East Bolaang Mongondow, Indonesia: A cross-sectional study - Tumurang, Marjes Netro; Watung, Grace Irene Viodyta; Langingi, Ake Royke Calvin (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by insulin resistance and progressive β-cell dysfunction, leading to long-term complications that negatively affect patients’ quality of life (QoL). Various demographic, psychological, and clinical factors influence QoL. However, limited research has explored these associations within the sociocultural context of a rural regency in Indonesia, where variations in healthcare access, education, and economic conditions may uniquely affect QoL. Objective: This study aimed to examine the relationships between clinical and demographic factors and QoL among patients with T2DM. Methods: A cross-sectional study was conducted from June 2024 to February 2025 with 1,030 adult T2DM patients recruited via purposive sampling. QoL was assessed using the Diabetes Quality of Life Scale (DQOL), and anxiety was measured using the State-Trait Anxiety Inventory (STAI). Additional data on employment status, disease duration, age, and therapy type were collected via structured questionnaires. Data were analyzed using SPSS 27 with univariate, bivariate (chi-square), and multivariate logistic regression analyses. Statistical significance was set at p < 0.05. Results: Descriptively, most participants were female (90.8%), aged 51–60 years (59.7%), and had completed senior high school (84%). Overall, 61.2% reported good QoL. Anxiety was mild in 73.3% and moderate in 26.7% of participants. Multivariate logistic regression indicated that moderate anxiety (OR = 2.78; 95% CI [1.48–5.25], p = 0.041), disease duration ≥5 years (OR = 10.24; 95% CI [2.13–12.40], p = 0.027), older age (≥50 years) (OR = 8.94; 95% CI [2.15–14.73], p = 0.032), unemployment (OR = 3.66; 95% CI [1.03–13.07], p = 0.030), and insulin therapy (OR = 11.3; 95% CI [2.80–12.60], p = 0.019) were significantly associated with poor QoL. The model showed good fit (Hosmer–Lemeshow χ² = 5.32, p = 0.72) and moderate explanatory power (Nagelkerke R² = 0.24). Conclusion: Longer disease duration, older age (≥50 years), unemployment, moderate anxiety, and insulin therapy were significantly associated with lower QoL among T2DM patients. These findings emphasize the need for integrated care strategies combining educational, psychosocial, and socioeconomic interventions. Nursing practice should prioritize holistic, patient-centered approaches incorporating psychological support, individualized education, and social empowerment.